AB0467 Sustained clinical response in refractory rheumatoid arthritis patients with a low-dose rituximab retreatment regimen. (12th June 2018) - Rodriguez García, S.D.L.C.; Castellanos-Moreira, R.; Hernandez-Miguel, M.V.; Cuervo, A.; Ruiz-Esquide, V.; Ramirez, J.; Camacho, O.; Cañete, J.D.; Gomez Puerta, J.; Sanmartí, R.
Abstract : Background: The standard dose of rituximab (RTX) in rheumatoid arthritis (RA) is two intravenous (iv) 1 g infusions, separated by two weeks. Recently, the efficacy of a low-dose of RTX for retreatment in RA patients has been reported. 1 Objectives: Our aim was to assess the long-term sustained effectiveness of a low-dose of RTX in daily clinical practice. Methods: Observational retrospective study including all RA patients treated on a tertiary hospital who had received at least one cycle of RTX, at the standard dose, between June 2006 and May 2017. We selected those patients who achieved a good or moderate EULAR response and thereafter were down-titrated to a low-dose regimen (1 g). Variables analysed: age, sex, disease duration, presence of ACPA (antiCCP2) and rheumatoid factor (RF), glucocorticoid (GC) and conventional synthetic DMARD (csDMARD) use and dosage before and after RTX treatment, number of biologic DMARD (bDMARD) used prior to initiating RTX. Disease activity was measured using DAS28 index (prior to first RTX infusion, at low-dose regimen initiation and at last follow-up visit). Results: 53 patients received, at least, one cycle of 2 g RTX, 70% achieved a good or moderate EULAR response and were stepped-down to a low dose re-treatment regimen. Baseline characteristics of patients receiving low-dose RTX were: mean age 56.4±10.9 years; 13.5% male, mean disease duration 12.7±9.8 years, 91.9% RF +and 97.3% ACPA +; mean DAS28 prior to RTX initiation 5, 79±1, 17. 73% of patients had received other bDMARD before RTX, 48% 2 or more. 92% were on cs-DMARDs, 51.4% methotrexate (MTX) and 37.8% leflunomide (LEF) and 86.5% were receiving concomitant GC (median dose 10 mg, P25–75 5–10 mg). 73% of subjects received only one standard cycle before RTX dose reduction. Mean DAS28 decreased significantly between the first visit on 1 g RTX vs the last follow-up visit (4.08 vs 3.04; p<0.0001). Additionally, 11 patients (8 MTX, 3 LEF) were able to reduce csDMARD dosage, 56.3% of patients receiving GC at the initiation of low-dose retreatment were able to reduce the dose (median 10 mg vs 5 mg; p<0.0001), and 28% discontinued GC therapy. After a mean follow-up of 3±1.8 years, RTX was withdrawn in 10 patients: 8 due to adverse events (recurrent infections in 4) and 2 cases due to loss of efficacy. Conclusions: A sustained clinical response was observed with the 1 gr retreatment of RTX after a long-term follow-up period. Reference: [1] Mariette X, et al. Ann Rheum Dis2014;73:1508–14. Disclosure of Interest: None declared